THE EFFECT OF USING GIST STRATEGY THROUGH RECOUNT TEXT TOWARD STUDENTS’ READING COMPREHENSION AT ASY-SYUKRIYYAH COLLEGE - Destiani Rahmawati (Jurnal Asy-Syukriyyah, 2020)
The lecturer found some constraints in students of understanding English text such as limited vocabulary, the students were lack of stock of the words, the students who have little knowledge of vocabulary will face some difficulties to understand the written language. The students` lack of knowledge about the text, they are hard to understand what the text tells about it. This research used Experimental design. The writer has taught two different classes at Asy-Syukriyyah College in Tangerang. They were control and experimental class. The population of this research is 100 students that consist of two classes. The writer used cluster random sampling technique to measure the reading comprehension test. In collecting data, the writer will give reading comprehension test to the students using multiple choice, questioners in teaching learning using GIST strategy in reading comprehension. The test has given to get the objective data of student`s achievement in reading comprehension by using GIST strategy in experiment class. The writer would apply two test: there are pre-test and post-test. Students reading comprehension increased after given treatment by using GIST strategy of experiment class. Based on the data analysis of post-test, it has shown that values t count more than t table, where t count was 2.18 while t table was 1.99, so hypothesis statistic   (H1) was accepted.  This suggest that GIST strategy was more effective than conventional learning.